Microbial degradation and valorization of food wastes: waste to wealth approaches towards sustainability - Satarupa Dey; Avishek Talukdar; Sayan Bhattacharya (Discover Chemistry)
Abstract Changing life style, urbanization and rapid increase in global population have led to the increase in the generation of food waste from household, industrial and agricultural sectors. Different surveys done by Food and agricultural organization have shown that nearly one third of the total food is annually wasted which causes serious environmental hazards when their disposal is concerned. Moreover, this also leads to wastage of useful and utilizable resources. Traditionally food wastes which are rich in organic matter is treated by landfilling and incineration which may generate toxic gases leading to severe environmental pollution and health hazards. Biological and microbial treatment of food waste can be ecofriendly and cost-effective processes of treatment. This review discusses microbial and enzymatic treatment processes of food waste, their utilization and valorization. Different types of microorganisms can be utilized for management of food waste and can be useful in the production of biofertilizers, bioplastics, electrical energy, biofuels and biosurfactants. Microbial and enzymatic processing of different types of food waste are sustainable, cost effective and eco-friendly ways of food waste management. The paper shows several sustainable technologies of food waste valorization, which are in synchrony with the Sustainable Development Goals (SDGs).